Building Rural Community Resilience Through Innovation and Entrepreneurship - French, Charlie (New York, NY : Routledge, 2022)
"Drawing from empirical analyses, case studies, and a synthesis of best practices, this book explores how innovation manifests itself in rural places and how it contributes to entrepreneurial development and resilience. Innovation in rural places may come about as a result of new forms of collaboration; policies that leverage rural assets and address critical service or product gaps, novel strategies for accessing financial capital; infusion of arts into aspects of community life; and cultivation of networks that bridge entrepreneurs, organizations, and institutions. The chapters illustrate how a number of innovation-related characteristics relate to economic vibrancy in rural places, such as a strong connection to the arts, adaptive and sustainable use of natural resources, value-chain integrated food systems, robust bridging social capital networks, creative leveraging of technology, and presence of innovation-focused entrepreneurs. Through exploration of these and other topics, this book will provide insights and best practices for rural community and economic development scholars and practitioners seeking to strengthen the rural innovation ecosystem"--
Includes bibliographical references and index.
Keywords: Land use, Rural -- Environmental aspects; Rural development -- Planning; Community development -- Environmental aspects; Entrepreneurship -- Technological innovations